Foundation of an affective tutoring system: learning how human tutors adapt to student emotion. (25th February 2008) - Alexander, Samuel; Sarrafzadeh, Abdolhossein; Hill, Stephen
The developing field of Affective Tutoring Systems (ATSs) has created a need to understand how such tutoring systems should adapt to the emotional state of students. To this end, an observational study of human tutors was conducted to learn how human tutors adapt to the affective state of students. This knowledge can then be used to implement the tutoring strategies of an ATS and is hence a critical foundation in its development. This paper presents the methodology and results of this observational study of human tutors and looks ahead to the future development of an animated pedagogical agent capable of detecting, expressing and adapting to emotion.